Business Performance: The Role of Managerial Competence and Supply Chain Management Practices of Coffee Shops in Medan Cit - Ismoyo, Ari; Martial, Tri; Simanullang, Endang Sari (JURNAL AGRICA, 2025)
Coffee Shop represents the final stage of the coffee agribusiness subsystem, serving as the producer of processed coffee products for consumers. The Coffee Shop business in Medan has grown and developed in various ways. The intense competition among Coffee Shops in Medan has affected business performance. Some have even ceased operations and eventually closed. This study aims to analyze  the influence of managerial competence and supply chain management practices on the business performance of Coffee Shops in Medan. The research employs a descriptive quantitative approach using questionnaires. Data is analyzed using Structural Equation Modeling - Partial Least Squares Second Order, as the variables in managerial competence and supply chain management practices are multidimensional. Respondents were selected using the purposive sampling method with a total of 35 respondents, coffee shop managers or business owners in Medan City with several criteria. The results indicate that managerial competence has a significant positive effect on supply chain management practices and a significant positive effect on business performance. Meanwhile, supply chain management practices in the coffee shop business do not have a significant effect on performance. Supply chain management practices have not been effective in reducing coffee raw material costs. Therefore, to improve business performance, business owners can increase sales volume by focusing on implementing marketing mix strategies